2021
DOI: 10.1186/s12903-021-01805-8
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation following chitosan-based varnish or chlorhexidine-fluoride varnish application in patients undergoing fixed orthodontic treatment: a double blinded randomised controlled trial

Abstract: Background Orthodontic treatment poses an increased risk of plaque accumulation and demineralisation of enamel leading to white spot lesion around the brackets. This parallel arm trial aims to assess the degree of bacterial plaque formation adjacent to orthodontic brackets, following the application of a chitosan-based varnish or chlorhexidene-fluoride varnish. Methods A total of 200 teeth from 20 patients undergoing fixed orthodontic therapy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…It effectively inhibited plaque formation by forming flocs as the bridges (bridges formed between positively charged chains that attach to the microbial wall) become effective, thus inhibiting S. mutans. The activity of CS was compared to chlorhexidine fluoride varnish, which is known as a chemotherapeutic agent and was found to be similar [76]. The electrostatic interaction between the positively charged CS molecules and the microbe surface negatively charged is the most widely acknowledged mechanism for microbial inhibitions [77].…”
Section: Anti-microbial Activity Of Csmentioning
confidence: 99%
“…It effectively inhibited plaque formation by forming flocs as the bridges (bridges formed between positively charged chains that attach to the microbial wall) become effective, thus inhibiting S. mutans. The activity of CS was compared to chlorhexidine fluoride varnish, which is known as a chemotherapeutic agent and was found to be similar [76]. The electrostatic interaction between the positively charged CS molecules and the microbe surface negatively charged is the most widely acknowledged mechanism for microbial inhibitions [77].…”
Section: Anti-microbial Activity Of Csmentioning
confidence: 99%
“…Fixed orthodontic appliances remain the prevailing orthodontic treatment for most malocclusions. 38 Systematic reviews on lingual braces have concluded that these appliances did not survive the drawback of intraoral irritation and increased difficulty with speaking and eating. 39 Whereas there is relatively little development of the lingual appliances used in everyday orthodontics, CAT seems to be an area of constant improvement and increasing demand.…”
Section: Aligners Versus Fixed Appliances In Adult Orthodonticsmentioning
confidence: 99%
“…Fixed multibracket orthodontics is the most widely used system in orthodontic treatments, whether by conventional, low friction or lingual brackets. Despite its multiple advantages in solving cases of dental malocclusions, it can also be associated with adverse side effects such as the appearance of lesions in the enamel, facilitated by the accumulation of plaque and oral bacteria in the bracket, the adhesive or the surface of the enamel itself [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intra treatment methods have included varnishes or toothpastes with chlorhexidine or fluorine [ 3 , 20 , 21 ], adhesives of brackets with or without bioactive fluorinated ceramic [ 22 ] use of nanoplatinum particles in sealants around the brackets, mouthwashes, pastes and dental adhesive [ 23 , 24 , 25 ], organoselenium sealants [ 26 ], etc. None of these methods seems to have a superior efficacy over the others in preventing the appearance of white spots during orthodontic treatment [ 5 , 25 ].…”
Section: Introductionmentioning
confidence: 99%